KEBERGANTUNGAN PENGKOTBAH TERHADAP PERAN ROH KUDUS DALAM PERSIAPAN DAN PENYAMPAIAN FIRMAN TUHAN - Suriawan Suriawan (Sekolah Tinggi Theologia Abdiel, 2018)
The sermon is one of the central activities of the church liturgy. The role of the sermon is very important in the Christian ministry, but now we have found several problems of the sermon at the church pulpit. Nowadays, the preacher can easily get the material resources either from books or electronic journal and so on to prepare the sermon. But unfortunatelly, there are many sermons that cannot be applied in daily life or in the other word, such sermons have the poor application. This article wants to emphazise the role of the Holy Spirit for the preacher in preparing the sermon. Why do we need to depend on the role of the Holy Spirit in preparing the sermon? What do mean that we need to depend on the power of the Holy Spirit? These questions above will be discussed in this paper.